More on livelihoods - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Two new courses on sustainable livelihood approaches are on offer at the University of East Anglia in the UK. The course on Land Degradation and Sustainable Rural Livelihoods: Field Assessment runs from 28 April to 12 May 2003 and continues at...